Calculating InN/GaN Transmission Coefficient from Single Barrier to Five Barriers with Propagation Matrix and Transfer Matrix Methods - Ishmah Ulya; Russell Ong; Yuan Alfinsyah Sihombing (Physics Study Programme, Faculty of Science and Technology UIN Syarif Hidayatullah Jakarta, 2022)
In this study, the value of transmission coefficient on InN/GaN semiconductor from a single barrier to five barriers was determined by using the propagation matrix method and the transfer matrix method. This study aims to see the effect of adding a barrier to the number of resonance tunneling that occurs, to see the difference in transmission coefficient values which was obtained with the two methods, and to determine the effectiveness of the program execution process time from the propagation matrix and transfer matrix methods using Matlab programming. The results obtained indicated that the value of the transmission coefficient obtained from the two methods was the same. As the number of barriers increases, the number of resonance tunneling that occurs will increase. These two matrix methods had differences in terms of the effectiveness of the program execution process time and calculation process. The propagation matrix method was considered more effective than the transfer matrix method.